Perlindungan Hukum terhadap Tersangka dalam Perspektif Hak Asasi Manusia - Riswinarno, Harmaji; Suratman, Teguh (Jurnal Cakrawala Hukum, 2018)
This research is about legal protection in the perspective of human rights rights of suspects and potential violations in criminal case investigations. The purpose is to protect the rights of suspects, ensure legal certainty and avoid ill-treatment, and know the obstacles. This research is an empirical legal research. Research location at Sidoarjo Regional Police Station. Data analysis using descriptive qualitative, using content analysis techniques. Legal protection of suspect rights in criminal case investigations can be realized properly if there is a commitment to enforce the law seriously, and the community also provides control to reduce potential human rights violations. In Law Number 8 of 1981 concerning the Criminal Procedure Code as a basis, the examination process at the Sidoarjo Regional Police, investigators in the case of investigations of suspects pay attention to their human rights, give freedom to use a Legal Advisor, give freedom when answering investigator questions, do not emphasize when conducting examinations, notify legal counsel or family if the suspect is ill in custody, treats well when investigating. How to cite item:Â Riswinarno, H., & Suratman, T. (2018). Perlindungan Hukum terhadap Tersangka dalam Perspektif Hak Asasi Manusia.Â Jurnal Cakrawala Hukum, 9(1), 31-39. doi:https://doi.org/10.26905/idjch.v9i1.2203